2020
DOI: 10.1021/acssuschemeng.0c01106
|View full text |Cite
|
Sign up to set email alerts
|

Natural Pigments and Biogas Recovery from Microalgae Grown in Wastewater

Abstract: This study assessed the recovery of natural pigments (phycobiliproteins) and bioenergy (biogas) from microalgae grown in wastewater. A consortium of microalgae, mainly composed by Nostoc , Phormidium , and Geitlerinema , known to have high phycobiliproteins content, was grown in photobioreactors. The growth medium was composed by secondary effluent from a high rate algal pond (HRAP) along with the anaerobic digestion centrate, which aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Oxygen is generated through photosynthesis and used by heterotrophic aerobic bacteria to degrade the organic matter present in the water. This way, these systems have the capacity of treating wastewater efficiently whereas producing microalgae biomass which, after an appropriate harvesting/separation technique from the aqueous phase, can be further profited to produce bioenergy (biogas) or other added-value bioproducts such as pigments, biofertilizers or bioplastics [5][6][7][8][9]. In consequence, if this biomass is managed properly, the waste generated during microalgae treatment (biomass) is considerably reduced, as well as the operation and maintenance costs when compared to conventional WWTPs.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen is generated through photosynthesis and used by heterotrophic aerobic bacteria to degrade the organic matter present in the water. This way, these systems have the capacity of treating wastewater efficiently whereas producing microalgae biomass which, after an appropriate harvesting/separation technique from the aqueous phase, can be further profited to produce bioenergy (biogas) or other added-value bioproducts such as pigments, biofertilizers or bioplastics [5][6][7][8][9]. In consequence, if this biomass is managed properly, the waste generated during microalgae treatment (biomass) is considerably reduced, as well as the operation and maintenance costs when compared to conventional WWTPs.…”
Section: Introductionmentioning
confidence: 99%
“…This is expected because the GreenDune biomass samples grow under suboptimal conditions subjected to competition from different microalgal species but also to grazing due to the presence of predatory or parasitic (micro)organisms. These effects leave a lower proportion of biodegradable organic matter on the volatile solids of the biomass which, after predation or parasitism, consists of material richer in recalcitrant organics, with a lower availability of biodegradable organic matter for anaerobic digestion [32].…”
Section: Biogas Productionmentioning
confidence: 99%
“…Longhurst et al (2019) [131] have done exactly that in a UK case study and have concluded that these bio-fertilisers pose negligible risks to human, animal, environmental and crop receptors, when the appropriate stipulated risk management controls are adhered to. Ferreira et al (2018 [37,38] experimented with the algal-bacterial treatment of different types of wastewater streams-swine, cattle, poultry, dairy, brewery and urban-to grow microalgae which was subsequently dark-fermented to yield bioproducts, while Wicker et al (2020) [39] treated nutrient-rich liquid digestate with a microalgal-bacterial consortia to accomplish the triple objectives of wastewater treatment, nutrient recovery for reuse in agriculture and cultivation of biomass to be put to multiple uses [40]. Waste streams with higher nutrient concentrations resulted in a marked improvement in the microalgal productivity [37,38,41].…”
Section: Municipal and Industrial Solid Waste And Sewage Managementmentioning
confidence: 99%